Dinamika Politik Pasca Amandemen UUD NRI 1945 : Evaluasi Pemakzulan Presiden berdasarkan Putusan Justisil dan Keputusan Politik - Warsito; Widodo Budidarmo (UNES Law Review, 2023)
The procedure for dismissing the President, which is often referred to as impeachment, is an action that is natural in the presidential system. The demand for the dismissal of the President and Vice President halfway because of government policies that were considered impartial to the people at that time became a controversial act. This is because, after the amendment of the Constitution of the Republic of Indonesia Year 1945 (UUD NRI 1945) regarding the impeachment procedure and mechanism is still quite complicated and does not have a comprehensive regulation regulating the impeachment mechanism of the President and or Vice President. Article 7B of the 1945 NRI Constitution only specifies in general terms the impeachment mechanism for the President. This difficult stage must be motivated because the President has violated the constitution. Therefore, in this study, the author will elaborate in more detail regarding the impeachment mechanism against the President Justisil Verdicts and Political Decisions.